The Effect of Demographic Factors on Work-related Injuries in the Oil and Gas Industry in the Niger Delta Region in Nigeria - Oseibhi Oyamienlen; Ify L. Nwaogazie; Chinemerem Patricks (Archives of Current Research International, 2023)
This study aimed to find out the effect of Demographic factors on work-related Injuries in the Oil and Gas Industry in the Niger Delta Region in Nigeria. The research method that was used for this study was a correlation design to test the demographic variables and how related they were to work-related injuries The instrument used for this study was a well-structured questionnaire on Analysis of Work-related Accidents which was sent to e-mails of oil and gas workers in Akwa Ibom state and the Rivers state of Nigeria for the collection of data to provide answers to the questions. The reliability of the instrument was assessed using Cronbach’s alpha which was 0.767, Different statistical test methods (Mann-Whitney, Kruskal Wallis, z-test, ANOVA and Dunn’s test) were used. The findings revealed that gender does not play any significant role in work-related injuries with p-values greater than 0.05, Education plays a role in certain types of injuries i.e. (contusion and MSDs with P-values of 0.013 and 0.015 respectively, and musculoskeletal disorders were the common types of injuries experienced by staff with a p-value of 0.05. Fractures and Amputations were experienced by workers who have spent above 16 years working offshore with p-values of 0.031, 0.035 and 0.020, 0 & 022 respectively. In Summary, certain demographic factors have effect on work-related Injuries.